2005
DOI: 10.1111/j.1432-2277.2005.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inadequate in situ perfusion in the non heart-beating donor

Abstract: Summary In situ aortic perfusion in the nonheart‐beating donors (NHBD) is an important procedure to reduce primary warm ischaemic injury prior to formal donor organ retrieval. It allows an interim period to obtain donor family consent and theatre preparation. This study describes our experience of inadequate aortic perfusions resulting from difficult aortic cannulations and associated adverse outcome despite reasonable viability tests. Since 1998, all NHBD in our institution are perfused in situ using a doubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…The main reason for discard was poor kidney quality after preservation. In 12 of the kidneys from the DBTL group, the flush-out was poor, resulting in a blue congested kidney, as also described by others 17 . This may have been due to insufficient flushing during perfusion through the catheter.…”
Section: Discussionsupporting
confidence: 51%
“…The main reason for discard was poor kidney quality after preservation. In 12 of the kidneys from the DBTL group, the flush-out was poor, resulting in a blue congested kidney, as also described by others 17 . This may have been due to insufficient flushing during perfusion through the catheter.…”
Section: Discussionsupporting
confidence: 51%
“…In this present report, both kidneys appeared pink and healthy throughout EVNP. Furthermore, the level of renal blood flow and urine output were within range of EVNP parameters in kidneys from our clinical series, suggesting their suitability for transplantation (3).…”
supporting
confidence: 67%
“…Platelets adhering to the vascular endothelium can induce endothelial apoptosis and aggravate reperfusion injury after transplantation 4. Gok et al reported an exceptionally high rate of primary nonfunction from inadequately perfused kidneys: 66.7% compared with 4.8% in those with adequate perfusion 9. Therefore, there is much reluctance to use these organs.…”
Section: Discussionmentioning
confidence: 99%